2001
DOI: 10.1007/s10228-001-8160-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in the Japanese rosy bitterling, Rhodeus ocellatus kurumeus (Cyprinidae)

Abstract: Comparison of meristic characters (pored lateral line scales, vertebrae, and fin rays), and PCR-RFLP analysis in the D-loop and ND1 regions of mitochondrial DNA were performed to estimate the genetic diversity in local populations of the Japanese rosy bitterling, Rhodeus ocellatus kurumeus. In terms of meristic characters, the Fukuoka population was the largest in both range and variance of the number of pored lateral line scales and vertebrae (abdominal and caudal), and Osaka was the second, whereas the Kagaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…In such cases, temporal reductions in fish population size are likely to have occurred, with consequent loss of genetic diversity through a bottleneck. Loss of n and k, numbers of fish examined and haplotypes, respectively genetic diversity in the mitochondrial genome has also been reported for Rhodeus ocellatus kurumeus populations isolated in small ponds (Kawamura et al, 2001). Kawamura et al (2001) revealed that such populations in closed water systems showed complete monomorphism, although genetic diversity persisted in those inhabiting open water systems.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In such cases, temporal reductions in fish population size are likely to have occurred, with consequent loss of genetic diversity through a bottleneck. Loss of n and k, numbers of fish examined and haplotypes, respectively genetic diversity in the mitochondrial genome has also been reported for Rhodeus ocellatus kurumeus populations isolated in small ponds (Kawamura et al, 2001). Kawamura et al (2001) revealed that such populations in closed water systems showed complete monomorphism, although genetic diversity persisted in those inhabiting open water systems.…”
Section: Discussionmentioning
confidence: 86%
“…The noncoding control region is generally considered as one of the most variable regions in mitochondrial genomes (Meyer, 1993), although Kawamura et al (2001) reported, by PCR-RFLP analysis, that genetic diversity quantified for the control region was approximately half of that for the NADH subunit 1 region. In the present study, using the cytochrome b gene and the control region sequence data, we tried to evaluate the extent of genetic diversity in wild and reared populations of T. tanago, in addition to annual changes in diversity through captive breeding.…”
mentioning
confidence: 98%
“…Recent population decline due to human impact, such as habitat fragmentation, may also cause bottlenecks, as suggested for some endangered cyprinids (Ohnaka et al, 1999;Kawamura et al, 2001). However, it is difficult to explain fixation to a single haplotype throughout disjunct populations, as seen in the bagrid fishes.…”
Section: Discussionmentioning
confidence: 94%
“…Sequences of haplotype mt1 have been deposited in DDBJ/EMBL/GenBank under Accession nos AB2367315 in D-loop and AB236732 in ND1. For further technical details, including PCR, restriction digest and gel run conditions see Kawamura et al (2001).…”
Section: Study Area and Sample Collectionsmentioning
confidence: 99%